Clinical manifestation score and characterization of cytokines and lymphocytes of dimethylacetamide-induced toxic hepatitis in spandex workers. (April 2023) - Wang, Jinglei; Tang, Kai; Wang, Caiping; Xu, Shengzhi; Wang, Yaqin; Zhu, Qinya
Occupational exposure to dimethylacetamide (DMAc) has been reported to cause toxic hepatitis. Sixty spandex workers were included in this study to research the clinical manifestations and expression of cytokines and lymphocytes in DMAc-induced toxic hepatitis. Chinese drugs (reduced glutathione and Hugan tablets) were used to treat them. The manifestations including jaundice, asthenia, appetite, nausea, emesis, abdominal distension, yellow urine, and dizziness were scored. The percentages of patients rated as 0–3, 4–6, 7–9, and 10–12 points were 33.3%, 43.3%, 21.7%, and 1.7%, respectively, before treatment, and all patients showed 0–3 points after the treatment. The ultrasonic and CT imaging revealed diffuse intrahepatic hypodensity, intrahepatic calcification, signs of liver injury, and splenomegaly, which improved after therapy. Blood analysis showed that ALT, AST, TBIL, IL-6, IL-10, TNF-α, IFN-γ, CD3 + %, and CD4 + /CD8 + statistically decreased after drug treatment. Correlation analysis demonstrated positive linear correlations between ALT and TBIL, AST and TBIL, IL-10 and ATL, IL-10 and AST, IL-10 and TBIL, IFN-γ and IL-6, IFN-γ and TNF-α, and CD3 + % and ALT. Pro-inflammatory cytokines and lymphocytes in DMAc-induced toxic hepatitis reflected an active immune state that decreased after treatment. IL-10 may inhibit the immune response in this disease, as a protective mechanism.